2019
DOI: 10.3389/fpls.2018.01902
|View full text |Cite
|
Sign up to set email alerts
|

Over-Expression of a Maize N-Acetylglutamate Kinase Gene (ZmNAGK) Improves Drought Tolerance in Tobacco

Abstract: Water deficit is a key limiting factor that affects the growth, development and productivity of crops. It is vital to understand the mechanisms by which plants respond to drought stress. Here an N-acetylglutamate kinase gene, ZmNAGK, was cloned from maize (Zea mays). ZmNAGK was expressed at high levels in maize leaves and at lower levels in root, stem, female flower and male flower. The expression of ZmNAGK was significantly induced by PEG, NaCl, ABA, brassinosteroid and H2O2. The ectopic expression of ZmNAGK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Transient expression among the poor RILs suggests a potential interruption of growth. In the other poor RILs, the OsCML27 cohorts also included downregulated genes associated with stress adaptation such as OsFBK12 (Os03t0171600-02; Delayed senescence Kelch-repeat F-box protein), OSISAP1 (Os09t0486500-02; Cold, drought and salt tolerance-associated A20/AN1 zinc-finger), OsPLC4 (Os05t0127200-02; Salt and dehydration regulated Phospholipase C4), OsNAGK1 (Os04t0550500-05; Drought-regulated N-acetylglutamate kinase-1), OsMST6 (Os07t0559700-00; Monosaccharide transporter involved in water retention and membrane stability), and OsHrd3 (Os03t0259300-01; Unfolded protein and apoptosis response; Supplementary Dataset 3 ) ( Mukhopadhyay et al, 2004 ; Chen et al, 2013 ; Ohta and Takaiwa, 2015 ; Deng et al, 2019 ; Liu et al, 2019a ). The superiority of the FL510 OsCML27 network is further illustrated by the distinct upregulation of OsIAA1 (Os01t0178500-02; auxin repressor AUX/IAA1), suggesting the interruption of auxin-mediated growth signaling in the poor RILs ( Song et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…Transient expression among the poor RILs suggests a potential interruption of growth. In the other poor RILs, the OsCML27 cohorts also included downregulated genes associated with stress adaptation such as OsFBK12 (Os03t0171600-02; Delayed senescence Kelch-repeat F-box protein), OSISAP1 (Os09t0486500-02; Cold, drought and salt tolerance-associated A20/AN1 zinc-finger), OsPLC4 (Os05t0127200-02; Salt and dehydration regulated Phospholipase C4), OsNAGK1 (Os04t0550500-05; Drought-regulated N-acetylglutamate kinase-1), OsMST6 (Os07t0559700-00; Monosaccharide transporter involved in water retention and membrane stability), and OsHrd3 (Os03t0259300-01; Unfolded protein and apoptosis response; Supplementary Dataset 3 ) ( Mukhopadhyay et al, 2004 ; Chen et al, 2013 ; Ohta and Takaiwa, 2015 ; Deng et al, 2019 ; Liu et al, 2019a ). The superiority of the FL510 OsCML27 network is further illustrated by the distinct upregulation of OsIAA1 (Os01t0178500-02; auxin repressor AUX/IAA1), suggesting the interruption of auxin-mediated growth signaling in the poor RILs ( Song et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…SlNAGS1 enhances tolerance to drought and salt stress in Arabidopsis, which is associated with the accumulation of ornithine, a precursor of arginine ( Kalamaki et al., 2009 ). Overexpression of Z. mays N-acetylglutamate kinase ( ZmNAGK ), which phosphorylates NAG to proceed to arginine metabolism, in Nicotiana tabacum , resulted in greater resistance to drought stress than in wild-type plants with the accumulation of arginine, leading to the hypothesis that exogenous treatment with NAG modulates several environmental stress factors, including oxidative stress, with the activation of arginine metabolism as well as gene regulation activity involving stress-response genes ( Liu et al., 2018 ). In response to heat stress, NO synthesised during arginine metabolism transduces the heat stress signal from the shoot apex to the roots to enhance systemic resistance by upregulating heat stress-response genes in Arabidopsis ( He et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, maize plants overexpressing ZmNAGK aggregated more arginine in response to SAL treatment under osmotic stress conditions. Liu et al ( 2019 ) reported that enhanced expression of the ZmNAGK gene promoted drought endurance via greater water preservation, antioxidant defense capability, less oxidative damage, and aggregation of more arginine.…”
Section: Discussionmentioning
confidence: 99%